2022
DOI: 10.1038/s41371-022-00710-z
|View full text |Cite
|
Sign up to set email alerts
|

The World Hypertension League Science of Salt: a regularly updated systematic review of salt and health outcomes studies (Sept 2019 to Dec 2020)

Abstract: The World Hypertension League Science of Salt health outcomes review series highlights high-quality publications relating to salt intake and health outcomes. This review uses a standardised method, outlined in previous reviews and based on methods developed by WHO, to identify and critically appraise published articles on dietary salt intake and health outcomes. We identified 41 articles published between September 2019 to December 2020. Amongst these, two studies met the pre-specified methodological quality c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 88 publications
1
6
0
Order By: Relevance
“…Our findings in Figure 2 elucidated that those participants with higher intakes of sodium, energy, fat, and protein showed larger HRs of hypertension risk, despite the fact that the p-value for interaction was only shown for dietary fat intake. High intake levels of dietary salt and sodium have been generally considered as risk factors for hypertension [49]. Consistently, in our study, those participants with a higher level of sodium intake showed a slightly higher incidence of hypertension, which perhaps contributed to the larger HR of BCAAs among these people.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings in Figure 2 elucidated that those participants with higher intakes of sodium, energy, fat, and protein showed larger HRs of hypertension risk, despite the fact that the p-value for interaction was only shown for dietary fat intake. High intake levels of dietary salt and sodium have been generally considered as risk factors for hypertension [49]. Consistently, in our study, those participants with a higher level of sodium intake showed a slightly higher incidence of hypertension, which perhaps contributed to the larger HR of BCAAs among these people.…”
Section: Discussionsupporting
confidence: 88%
“…31 Blood pressure varies with dietary salt interventions, a phenomenon that has been demonstrated in hundreds of human randomized controlled trials. 32 Huang et al conducted a systematic evaluation and meta-analysis to explore the dose-response relationship between dietary sodium reduction and alterations in blood pressure. 33 They included 133 randomized trials involving 12 197 subjects.…”
Section: Hypertensionmentioning
confidence: 99%
“…A high sodium intake is one of the leading dietary risk factors for mortality worldwide ( 1 ), accounting, globally, for 3.2 million deaths in 2017. Beyond the well-established relationship of high sodium intake and increased blood pressure (BP) and higher risk of cardiovascular diseases ( 2 ), other health outcomes such as chronic kidney disease and physical performance were also reported ( 3 ). One of the goals of the World Health Organization (WHO) “Global Action Plan for the Prevention and Control of Non-communicable Diseases 2013–2020” is to reduce population sodium intake by 30% ( 4 ).…”
Section: Introductionmentioning
confidence: 99%